Characterization of pseudacyclins A-E, a suite of cyclic peptides produced by Pseudallescheria boydii - Pavlaskova, Katerina; Nedved, Jan; Kuzma, Marek; Zabka, Martin; Sulc, Miroslav; Sklenar, Jan; Novak, Petr; Benada, Oldrich; Kofronova, Olga; Hajduch, Marian; Derrick, Peter J; Lemr, Karel; et al. (Journal of natural products, 2010)
Pseudallescheria boydii sensu lato is an emerging fungal pathogen causing fatal infections in both immunocompromised and immunocompetent hosts. In this work, two P. boydii isolates (human and animal origin) have been identified as being producers of cyclic peptides. Five putative nonribosomal peptides with a unique structure, which have been named pseudacyclins, were characterized by nuclear magnetic resonance spectroscopy and mass spectrometry. The most abundant representative of the pseudacyclins was quantified also on fungal spores. The presence of these peptides on inhaled fungal spores creates the possibility for exploitation of pseudacyclins as early indicators of fungal infections caused by Pseudallescheria species.
Keywords: nukleární magnetická rezonance biomolekulární; molekulární struktura; myši; sekvence aminokyselin; Molecular Structure; Microbial Sensitivity Tests; Amino Acid Sequence; Pseudallescheria; Nuclear Magnetic Resonance, Biomolecular; Animals; lidé; cyklické peptidy; Mice; Peptides, Cyclic; Humans; zvířata; mikrobiální testy citlivosti